Indicadores de gênero no periódico Scientometrics (1981-2017) - Godoi, Fábio dos Santos (2018)
Introduction – The scientific evaluation by indicators demands a reflection in addition to the quantitative data. Gender in science plays complex roles, gender indicators should include in their analysis the context of social, economic, and political interests that are intrinsic to the science structure. An analysis that shows a more comprehensive scenario should use references that relate the genders within its social structure. Therefore, the research question about this project asks how are the bibliometric and scientometric indicators of gender characterized in the journal Scientometrics? The aim was to conceptualize and describe the bibliometric and scientometric indicators that can express the gender issue in science articles published in the journal Scientometrics. Methodology – Scientific research has been shaped by descriptive bibliometrics, which comprises statistical techniques for extracting and indicators counting. The data source used was the academic journal Scientometrics. The search carried out through the subjects (keywords) without temporal delimitation. Thus, the corpus was composed of 177 articles covering the period from 1981 through the early part of 2017. The indicators used were the quantity and gender of the authors, the amount of references used, as well as the title, country, area, type of study, and keyword. Results – The data analysis was initially evaluated in three time-frames periods such as 1981–2000 (n=15), 2001–2008 (n=23) and 2009–2017 (n =139). The males amounted to 260 authors, on the other hand, the females added up to a total of 113 authors. The type of authorship was mostly co-authorship with 142 articles out of 177 totals. There were only 35 articles characterized as individual authorship. Regarding the cited references, about 22% (n=1712) contained reference related to gender and 78% (n=5992) contained references without gender issue. The countries with more applied research were the United States and Germany. The most frequent field of studies found was Mathematical sciences and Humanities. The majority of data were empirical research and the data sources most used by the articles were the multidisciplinary databases. Web of Science and Scopus stood out from all the rest. Conclusion – Even observing the first decades (1980, 1990 and 2000), coauthors were superior to individual articles. In addition, more than 90% of female authorships were in collaboration. The gender researches were more active in this current century, whereas they were the main issues to be searched. A good part of the main research on gender was due to the participation in women. The clear majority of men who dedicated to the study of gender had this variable incorporated into their research, but it was not the focus on the study.